Double dog dare - Graff, Lisa (Lisa Colleen), 1981- (Philomel Books, 2012)
When Kansas Bloom moves to California and joins the Media Club at school, he soon finds himself trying to outdo one of the other fourth-grade students in a "dare war" while vying for the job of on-air video homeroom announcer.